2015
DOI: 10.1590/2317-1545v37n4152357
|View full text |Cite
|
Sign up to set email alerts
|

Electrical conductivity test in Piptadenia moniliformis Benth. seeds

Abstract: -The electrical conductivity test is a quick, practical and objective test force; however, its effectiveness varies according to the species, quantity of seed, water volumes, soaking temperature, among other factors. The objective of this study was to evaluate the physiological quality of P. moniliformis seeds lots by means of the electrical conductivity test, testing different methodologies. For this, two lots were tested in three quantities of time (25, 50 and 75 seeds) and nine soaking times (2, 4, 6 , 12, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
1
2
0
1
Order By: Relevance
“…The increase of seeds number, setting the water volume, provides increase of electrical conductivity value (Tables 3 and 4). Pereira et al (2015) observed the same, what means, the electrical conductivity value increased when a higher number of seeds was used in the test. However, Lopes et al (2010) did not observed electrical conductivity increasing by increasing seeds number.…”
Section: Resultssupporting
confidence: 57%
“…The increase of seeds number, setting the water volume, provides increase of electrical conductivity value (Tables 3 and 4). Pereira et al (2015) observed the same, what means, the electrical conductivity value increased when a higher number of seeds was used in the test. However, Lopes et al (2010) did not observed electrical conductivity increasing by increasing seeds number.…”
Section: Resultssupporting
confidence: 57%
“…Com base nos resultados supramencionados, usou-se a temperatura de 25ºC para a comparação com o teste de condutividade elétrica, por causa da sua superioridade nos testes de vigor. Esse teste tem servido para avaliar a qualidade fisiológica de muitas espécies florestais (PEREIRA & MARTINS FILHO, 2012;TARGINO et al, 2015;DELAZERI et al, 2016;OLIVEIRA et al, 2016).…”
Section: Resultsunclassified
“…Water absorption curve and electrical conductivity: four replications with 50 seeds of each treatment were used, and the weight of each replication was measured on a precision analytical scale (0.001 g). Then, the seeds were put into properly identified plastic cups containing 75 mL of distilled water and placed in germination chamber, at 25 °C, with 12 h photoperiod (Pereira et al, 2015).…”
Section: Methodsmentioning
confidence: 99%